Shaping Future Entrepreneurs: Education, Intention, and the Adoption of AI - Utama, Iston Dwija; Inayati, Tutik; Setiawan, Margareth; Mohd, Zalena; Lusia, Erma (International Review of Management and Marketing, 2025)
Nowadays, technology cannot be separated from the business and education sectors, with Artificial Intelligence (AI) emerging as a vital tool for early-stage entrepreneurs. In higher education, students are increasingly expected to combine business knowledge with the ability to utilize digital tools, such as AI. However, the link between entrepreneurship education, entrepreneurial intention, and AI adoption for enhancing entrepreneurial capabilities remains underexplored. Using a purposive sampling method, data were collected from 175 valid respondents, and the model was tested using the structural equation model. The study found that entrepreneurial education and intention have a direct influence on the adoption of AI. Furthermore, AI adoption can mediate and enhance entrepreneurial competencies in the higher education context. The study offers theoretical insights into the integration of AI in the context of entrepreneurship education, providing practical implications that aim to prepare students for digital entrepreneurship.